1986
DOI: 10.1159/000457114
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate and Growth: Demonstration of a Growth Impairment and a Growth-Rebound Phenomenon

Abstract: Methylphenidate (MPH), the drug of choice in the treatment of attention deficit disorder with hyperactivity (ADD/H), has been shown to reduce the body stature of some patients. The present study was undertaken to determine if MPH suppresses growth in rats, and whether the clinical observation of a growth rebound phenomenon could be experimentally demonstrated. Our results demonstrate that neonatal rats treated with MPH show a reduction in femur length and a reduction in thyroid, pituitary, testis, adrenal glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
4
4
0
Order By: Relevance
“…These findings are in general agreement with prior studies showing that MP treatment of neonatal and adolescent rats results in dose dependent inhibition of weight gain [18,19,20]. In addition, the rapid normalization of both body weight and skeletal growth upon MP cessation is also in agreement with previous reports [19, 20].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are in general agreement with prior studies showing that MP treatment of neonatal and adolescent rats results in dose dependent inhibition of weight gain [18,19,20]. In addition, the rapid normalization of both body weight and skeletal growth upon MP cessation is also in agreement with previous reports [19, 20].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the rapid normalization of both body weight and skeletal growth upon MP cessation is also in agreement with previous reports [19, 20]. However, our results extend the basic findings of these prior studies by providing significantly more detailed measures of bone size, as well as densitometric and biomechanical data that reveal the extent to which MP treatment impairs skeletal development.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Body weights were comparable to concurrent controls at 5 weeks after cessation of dosing. A reduction in growth during dosing and growth-rebound phenomenon with cessation of MPH administration has been reported previously in juvenile rats (Pizzi et al, 1986(Pizzi et al, , 1987.…”
Section: Discussionsupporting
confidence: 70%
“…However, in children, it is well documented that MPH can cause anorexia and delayed growth (for review see [32]). Both animal and clinical studies have shown that the growth suppressing effects of MPH are acute and reversible after drug administration has stopped [29;30;33]. Even after individuals “catch up” on growth after discontinuation of MPH, our results on weight gain or arterial blood pressure point towards long-term effects on their reactivity to stressors.…”
Section: Discussionmentioning
confidence: 83%